Desenvolvimento de estação automatizada para secagem de moldes utilizados na vulcanização de borracha - Santos, Fernando dos (2014)
The industrial productive process, in a general way, has several losses. Some of them, inherent to the process, often are necessary to guarantee the final product’s quality. Others more hardly detected, and, mostly of the times without direct link with the product, end up by being absorbed by the production flow, or camouflaged by more impacting losses, which happens to occur in the same stage of production. The scope of the present study is the elimination of a loss source in the process, which in a not so clear way, but still logic, impacts negatively in the productivity: the drying of molds utilized in the vulcanization process for V-ribbed belts. Without a specific system, the drying process was made in the vulcanization, so that the station was no longer producing. Counting the time of stopped machine for mold drying, was observed how relevant this loss was, summed to the average time of stopped machine in a month for each vulcanization station. Thereby, the impacted stage of the process was studied, and in front of the definition of the real need, was proposed a solution of the developing of an automatic mold drying station. The project was elaborated fitting to the available resources in the site, and the vapor was selected as a middle of heating the mould for drying. The costs were raised, showed, and, definite the viability of the project, its execution and tests were registered. Finally, the impact in the productive process was also registered, assuring the real benefit of the implementation of the proposed solution.